Current Perspectives on the Etiology and Epidemiology of Retinitis Pigmentosa - o’g’li , Qo’ziyev Siddiqjon Rifat; Baxtiyorovna , Elmurotova Dilnoza; Shamansurova , Tukhtakhodjaeva Feruza (American Journal of Bioscience and Clinical Integrity, 2025)
Retinitis pigmentosa (RP) is a group of inherited retinal dystrophies characterized by progressive photoreceptor degeneration, leading to night blindness, peripheral vision loss, and eventual central vision impairment. RP affects approximately 1 in 4,000 individuals worldwide with significant genetic heterogeneity involving more than 60 identified genes. Current management strategies are largely supportive, including low-vision aids and retinal implants, but emerging gene-based therapies and stem-cell approaches have shown promising results in early clinical trials. This article reviews the epidemiology, pathophysiology, and current therapeutic approaches to RP, emphasizing recent advances in gene therapy and potential future directions.